2011
DOI: 10.1007/s10964-011-9702-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Identity Configurations: Three Studies with Adolescent and Emerging Adult Cohorts

Abstract: Adolescence and emerging adulthood are two core developmental periods in which individuals can develop a meaningful identity across domains. However, there is a lack of studies exploring correlates of different identity configurations. The purpose of this article was to fill this gap in examining correlates of configurations characterized by identity stability or instability in both ideological and relational domains or identity stability in one domain and instability in the other domain. Three studies were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 57 publications
(84 reference statements)
8
96
0
2
Order By: Relevance
“…As described by the participants in their narratives about returning to their birth country, a firm sense of self may be challenged throughout the lives of adoptees (Crocetti, Rubini, & Meeus, 2007;Crocetti et al, 2008;Crocetti, Scrignaro, Sica, & Margin, 2011). Growing up in a European country and having a Korean birth heritage made the participants feel as though a part of themselves was missing.…”
Section: Resultsmentioning
confidence: 99%
“…As described by the participants in their narratives about returning to their birth country, a firm sense of self may be challenged throughout the lives of adoptees (Crocetti, Rubini, & Meeus, 2007;Crocetti et al, 2008;Crocetti, Scrignaro, Sica, & Margin, 2011). Growing up in a European country and having a Korean birth heritage made the participants feel as though a part of themselves was missing.…”
Section: Resultsmentioning
confidence: 99%
“…Komitmen mengarah pada proses menentukan pilihan yang dibuat oleh individu terkait dengan berbagai domain identitas yang disertai dengan rasa percaya diri terhadap pilihannya (Crocetti, Fermani, Pojaghi, & Meeus, 2011;Crocetti, Jahromi, & Meeus, 2012;Crocetti, Rubini, & Meeus, 2008). Komitmen dapat dianggap sebagai indikator pembentukan identitas yang berhasil (Crocetti, Klimstra, Hale, Koot, & Meeus, 2013;Crocetti, Scrignaro, Sica, & Magrin, 2012;Crocetti, Sica, Schwartz, Serafini, & Meeus, 2013).…”
Section: Model Tiga Dimensi Identitasunclassified
“…However, the lives of young people have changed radically in industrialized countries in past decades and influence the identity development (Arnett, 2007). The most important changes are linked to the transition into adult roles, such as transition to living independently, stable full-time work, marriage, and parenthood (Crocetti, Scrignaro, Sica, & Magrin, 2012). Emerging adulthood is a new conception of development for the period from late teens to the twenties and is defined as the period of trying out various possibilities before making final adult commitments, which can be exalting as well as distressing or confusing (Arnett, 2007).…”
Section: Emerging Adulthoodmentioning
confidence: 99%
“…More specifically, emerging adults should make decisions regarding their partner choices (Crocetti et al, 2012;Rostowski, 2005). It has been observed that the lack of a stable romantic relationship is becoming a frequent problem in intimate relationships.…”
Section: Emerging Adulthoodmentioning
confidence: 99%